Into the Gauntlet #10 - Haddix, Margaret Peterson (New York : Scholastic, 2010)
Amy and Dan Cahill learn an ultimate truth that reveals the Madrigal Mission's importance and the danger that their nefarious family members pose to the entire world.
Keywords: Siblings -- Fiction; Orphans -- Fiction; Ciphers -- Fiction; Secrecy -- Fiction; Fiction